Defining what constitutes a reliable dataset to test for hybridization and introgression in marine zooplankton: Comment on Choquet et al. 2020 "No evidence for hybridization between Calanus finmarchicus and C. glacialis in a subarctic area of sympatry". Issue 10 (22nd September 2021) - Parent, Geneviève J.; Plourde, Stéphane; Browman, Howard I.; Turgeon, Julie; Petrusek, Adam
Abstract: The article 'No evidence for hybridization between Calanus finmarchicus and C. glacialis in a subarctic area of sympatry' (Choquet et al. 2020) concludes that "no evidence supports a potential for hybridization between C. finmarchicus and C. glacialis ". We argue that the InDel markers used by Choquet et al. (2020) may have limited capacity to detect admixed genotypes between C. finmarchicus and C. glacialis due to an inappropriate choice of reference sample for each species during the marker development. We first review terms and concepts used in genetic classification using reference samples and describe problems associated with the selection of genetic markers in the context of possible hybridization. We reanalyze InDel genotypes provided with Choquet et al. (2017) and identified an admixed individual. We then contrast methods used by Choquet et al. (2017) and Parent et al. (2012) and explain how Parent et al. (2012) developed microsatellite markers capable of discriminating admixed genotypes from parental species. In this comment, we have identified a major issue that must be considered when selecting reference samples in the context of testing for possible hybridization.